Past and present resource availability affect mating rate but not mate choice in Drosophila melanogaster. (11th August 2018) - Tudor, Erin; Promislow, Daniel E L; Arbuthnott, Devin
Abstract : The choice of when to mate can change rapidly based on changes in the environment. We show that the mating rate of male fruit flies ( Drosophila melanogaster ) decreases when starved, but can rapidly increase when males find females in high-quality environments. Therefore, mating decisions can change quickly and are strongly influenced by changes in environment. Abstract: The choices of when, where, and with whom to mate represent some of the most important decisions an individual can make to increase their fitness. Several studies have shown that the resources available to an individual during development can dramatically alter their mating rate later in life, and even the choice of mate. However, an individual's surroundings and available resources can change rapidly, and it is not clear how quickly the redistribution of resources towards reproduction can change. To address this important question, we measured mating rate and mate choice among Drosophila melanogaster males that were manipulated in terms of both past resources (control vs. starvation) and the resources available during mate choice (food vs. no food). We found that males given access to ample resources prior to mate choice showed higher mating rates than those that were starved, in agreement with previous studies. However, we also found that this effect can be reversed quickly, as starved males given the opportunity to mate in a high-quality environment mated at frequencies equivalent to their fed counterparts. Although past and present resources affected mating rate, they did not affect mate choice, as males mated with high-quality females at high frequencies regardless of their condition and environment. Our results show that both current condition as well as the promise of future resources can dramatically influence individuals' investment into reproduction and that such mating decisions are extremely plastic and reliant on environmental cues.